A systematic review and meta-analysis of fish oil encapsulation within different micro/nanocarriers. Issue 8 (10th March 2022) - Khoshnoudi-Nia, Sara; Forghani, Zahra; Jafari, Seid Mahdi
Abstract: Fish oil is one of the most important sources of omega 3 polyunsaturated fatty acids (PUFAs), especially eicosapentaenoic acid and docosahexaenoic acid which are the most important PUFAs with several health benefits. However, PUFAs are prone to oxidation and have a poor water solubility which limits the use of fish oils into food formulations. Encapsulation techniques can be applied to overcome these challenges. There is a large number of published micro/nanoencapsulation papers, where each of them contains a limited number of wall materials, feed formulation, encapsulation technique, and storage conditions. Therefore, without systematic evaluation of the data extracted from available studies, the design of functional foods containing fish oil would not be very successful. The objective of this systematic review is a meta-analysis of published researches on the nano/microencapsulation of fish oil. A comprehensive literature search was performed between 1 October and 31 December 2019 with encapsulation, fish oil, and oxidative stability keywords. Overall, 39 qualified articles were selected for the statistical analysis. Based on the technique used for encapsulation, the fish oil-loaded carriers were classified into four main groups: (a) spray-dried particles; (b) freeze-dried particles; (c) electrospun fibers and electrosprayed capsules; and (d) other carriers prepared by supercritical antisolvent, gelation, liposomes, spray–freeze drying, and transglutaminase catalyzed cross-linking. The three most frequent methods applied for fish oil encapsulation were spray drying (42.86%), freeze drying (21.43%), and electrohydrodynamic (19.04%) methods, respectively. Averagely, the best encapsulation efficiency was obtained for electrohydrodynamic processes. Also, the combination of polysaccharide–protein based wall materials provided the best performance in terms of fish oil encapsulation efficiency.